A new approach for rebalancing of U-lines with stochastic task times using ant colony optimisation algorithm - Celik, Erkan; Kara, Yakup; Atasagun, Yakup (TAYLOR & FRANCIS LTD, 2014)
In real world, line balancing involves existing lines in existing factories and the line typically needs to be rebalanced rather than balanced. Rebalancing of a U-line can be defined as a changeover process from its initial configuration to a new configuration for a while due to the reasons such as demand variations, changes in product design and changes in task times, etc. This study defines U-line rebalancing problem with stochastic task times and proposes a solution procedure based on ant colony optimisation. The objective of the proposed algorithm is to minimise total cost of rebalancing which is the sum of task transposition costs, workstation opening/closing costs and operating costs of workstations for a particular planning horizon. A comprehensive experiment is conducted to generate problem instances and to compare rebalancing costs of U-lines by means of several factors. A total of 6600 rebalancing solutions are obtained and several comparisons are performed.
Keywords: ant colony optimisation algorithm; U-lines; stochastic task times; rebalancing; MODEL ASSEMBLY LINES; HEURISTIC ALGORITHM; BALANCING PROBLEM; Engineering; Operations Research & Management Science